Hydrogeochemistry characteristics and salinity of groundwater in Quaternary sediments in the coastal zone of Ha Tinh province - Truong, Phan Van (Vietnam Journal of Earth Sciences, 2015)
The coastal zone of Ha Tinh contains three main aquifers in the Quaternary sediments, including the upper Holocene (qh2), lower Holocene (qh1) and Pleistocene (qp). The groundwater is related to three main infiltrate sources of Ca-Na-HCO3, Ca-HCO3 and Mg-HCO3 type; marine source with Na-Ca-HCO3, Na-Ca, Cl-Na-HCO3 type and mixed source of Na-Ca-HCO3, Na-Ca, Cl-Na-HCO3 type. The relative concentrations of ions in qh1 aquifer and qp aquifer are in the order of (Na++K+)> Mg2+>Ca2+ and Cl->HCO3->SO42-. The highly soluble Mg2+ and Ca2+ discharged from host rock ,participating in the chemical compositions of the groundwater are much greater than HCO3- from rain and surface water having (Ca+Mg)/HCO3 ratio higher than 0,5. Other less soluble ions in soil and silicate salt have an average (Na++K+)/total cations ratio about 0.19. The fresh water distributes mainly in qh2 aquifer. The qp aquifer is salinized in an area of about 676 km2. The TDS concentrations in the groundwater is increased in dry season as compared to rainy season leading to, decreasing fresh water reservoir in the aquifers strongly effecting the local livelihood activities and socio-economic development. References Nguyễn Kim Cương, 1991: Địa chất thủy văn. Nxb. Khoa học và Kỹ thuật, Hà Nội, 268 trang. Cục Địa chất và Khoáng sản Việt Nam, 1997: Báo cáo thuyết minh bản đồ nước dưới đất tỉnh Hà Tĩnh tỷ lệ 1:200.000. Nguyễn Văn Đản, Võ Công Nghiệp, Đặng Hữu Ơn, 1996: Nước dưới đất các đồng bằng ven biển Bắc Trung Bộ, Hà Nội. Hoàng Văn Hưng, 2004: Bản đồ tiềm năng chất lượng nước ngầm toàn quốc tỷ lệ 1:1.000.000, Tuyển tập Báo cáo HNKH lần thứ 16, Trường Địa học Mỏ - Địa chất. Hà Nội. Đỗ Trọng Sự, 2001: Nghiên cứu đặc điểm thủy địa hóa nước dưới đất vùng ven biển Bắc bộ và Bắc Trung bộ, Đề án cấp Bộ Công nghiệp. Fetter C.W., 1993: Applied Hydrogeology, Oshkosh, America. Kim K, 2003: Long-term disturbance of ground water chemistry following well installation. Ground Water 41:780-789. Piper AM, 1944: A graphic procedure in the geochemical interpretation of water-analysis. Trans AM Geophys Union 25:914-923. Sami K, 1992: Recharge mechanisms and geochemical processes in a semi-arid sedimentary basin, Eastern Cape, South Africa. J Hydrology 139:27-48.